Oncologic outcomes of early adjuvant chemotherapy initiation in patients with stage Ⅲ colon cancer - Jeong, Woon Kyung; Shin, Je-Wook; Baek, Seong Kyu (Annals of surgical treatment and research, 2015)
Although adjuvant chemotherapy reduces the risk of disease recurrence in stage III colon cancer patients, published guidelines do not specify when it should be initiated. This study aimed to assess the effect of adjuvant chemotherapy initiation time on disease recurrence and survival in stage III colon cancer patients undergoing curative surgical resection. The medical records of stage III colon cancer patients undergoing curative resection between February 2004 and December 2009 were reviewed. Of the 133 enrolled patients, 27 (20.3%) began adjuvant chemotherapy within 3 weeks of surgery, whereas 106 (79.7%) did after 3 weeks following surgery. Patients receiving chemotherapy within 3 weeks of surgery were less likely to experience recurrences than those beginning treatment later (11.1% vs. 33%, P = 0.018). The mean disease-free survival of patients receiving adjuvant therapy earlier was 54.6 months, whereas that of patients with later treatment was 43.5 months (P = 0.014). However, no significant differences in overall survival were observed between the 2 groups. Adjuvant chemotherapy should be initiated as soon as a patient's clinical condition allows. Patients with stage III colon cancer may benefit from adjuvant chemotherapy initiated within 3 weeks of surgery.